Locomotor Performance in Highly-Trained Young Soccer Players: Does Body Size Always Matter? - Buchheit, M.; Mendez-Villanueva, A.; Mayer, N.; Jullien, H.; Marles, A.; Bosquet, L.; Maille, P.; Morin, J.-B.; Cazorla, G.; Lambert, P. (International Journal of Sports Medicine, 2014)
To examine the effects of body size on locomotor performance, 807 15-year-old French and 64 Qatari soccer players participated in the present study. They performed a 40-m sprint and an incremental running test to assess maximal sprinting (MSS) and aerobic speeds, respectively. French players were advanced in maturity, taller, heavier, faster and fitter than their Qatari counterparts (e.g., Cohen’s d=+1.3 and + 0.5 for body mass and MSS). However, when adjusted for body mass (BM), Qatari players had possibly greater MSS than French players (d=+0.2). A relative age effect was observed within both countries, with the players born in the first quarter of the year being taller, heavier and faster that those born during the fourth quarter (e.g., d=+0.2 for MSS in French players). When directly adjusted for BM, these MSS differences remained (d=+0.2). Finally, in both countries, players selected in National teams were taller, heavier, faster and fitter than their non-selected counterparts (e.g., d=+0.6 for MSS in French players), even after adjustments for body size (d=+0.5). Differences in locomotor performances between players with different phenotypes are likely mediated by differences in body size. However, when considering more homogeneous player groups, body dimensions are unlikely to substantially explain the superior locomotor performances of older and/or international players.
Keywords: association football; allometric scaling field tests; maturation